2000
DOI: 10.1046/j.1365-8711.2000.03797.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and infrared photometry of the Type IIn SN 1998S: days 11-146

Abstract: A B S T R A C TWe present contemporaneous optical and infrared (IR) photometric observations of the Type IIn SN 1998S covering the period between 11 and 146 d after discovery. The IR data constitute the first ever IR light curves of a Type IIn supernova. We use blackbody and spline fits to the photometry to examine the luminosity evolution. During the first 2±3 months, the luminosity is dominated by the release of shock-deposited energy in the ejecta. After ,100 d the luminosity is powered mostly by the deposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
142
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 38 publications
23
142
1
1
Order By: Relevance
“…No metals were seen at such high velocities. Fassia et al (2000) concluded that the IR excess at this epoch cannot, therefore, have been due to grain condensation in the ejecta. It must instead have been produced by an IR echo of the maximum-light luminosity from pre-existing dust in the CSM.…”
Section: Sn 1998s At Early Epochsmentioning
confidence: 95%
See 3 more Smart Citations
“…No metals were seen at such high velocities. Fassia et al (2000) concluded that the IR excess at this epoch cannot, therefore, have been due to grain condensation in the ejecta. It must instead have been produced by an IR echo of the maximum-light luminosity from pre-existing dust in the CSM.…”
Section: Sn 1998s At Early Epochsmentioning
confidence: 95%
“…A pre-discovery limiting magnitude of ∼+18 obtained on 1998 February 23.7 (Leonard et al 2000) indicates that SN 1998S was discovered within a few days of shock breakout. Following Chugai (2001), we adopt 1998 February 24.7 UT = JD 2 450 869.2, 6 d prior to discovery, as the explosion epoch, t = 0 d. Relative to this epoch, the zero epochs adopted by other authors are later by, respectively, +5 d (Leonard et al 2000), +6 d (Fassia et al 2000(Fassia et al , 2001Pooley et al 2002) and ∼+23 d (Bowen et al 2000;Gerardy et al 2000Gerardy et al , 2002a. Throughout this paper, epochs quoted from other authors have been shifted to our zero epoch definition.…”
Section: Sn 1998s At Early Epochsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wooden (1997) reiterates that the cause was CSM dust "echoing the light curve." Fassia et al (2000) reported a strong K − L excess in the emission from the Type IIn SN 1998S at 130 days. They attributed this to pre-existing CSM dust heated either by the SN luminosity (a conventional IR echo) or by X-rays from the CSM-shock interaction.…”
Section: The Warm Component: Early-phase Ir Excess Due To a Cdsmentioning
confidence: 99%